APAKAH SIFAT EXTRAVERSION DAN NEUROTICISM BERPENGARUH TERHADAP WHISTLEBLOWING? PENGUJIAN KOMITMEN SEBAGAI PEMEDIASI - Angeli Gavriel Tjahyadi; Andi Ina Yustina (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This research examines the effect of affective commitment as a mediation variable between the relationship of personality trait (extraversion and neuroticism) to whistleblowing. Data collection used web-based questionnaires and has collected 95 of respondents from individuals who work in the accountant's environment in the service, trade, and manufacturing industry in Indonesia. The researcher tested the hypotheses by using a Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Three of five hypotheses in this research are supported. The result of this research shows both personality trait, extraversion and neuroticism, affect to whistleblowing, and affective commitment not mediates the relationship between extraversion and neuroticism to whistleblowing.